An Indicator Measuring the Influence of the Online Public Food Environment: An Analytical Framework and Case Study - Cong, Na; Zhao, Ai; Kwan, Mei-Po; Yang, Jun; Gong, Peng (Frontiers in Nutrition, 2022)
The online public food environment (OPFE) has had a considerable impact on people’s lifestyle over the past decade; however, research on its exposure is sparse. The results of the existing research on the impact of the food environment on human health are inconsistent. In response to the lack of food elements in the definition of the food environment and the lack of a clear method to assess the health attributes and impact degree of the food environment, we proposed a new analytical framework based on the latest disease burden research, combining the characteristics of China's current food environment, from the perspective of environmental science. We redefined the food environment, and proposed that food and its physical space are two core elements of the food environment. Accordingly, we extracted four domains of characteristics to describe the basic components of the food environment. Using the sales records, we designed an approach by referring to the standard process of environmental health indicators, including the health attributes and the impact degree of the food environment, to measur the OPFE of takeaway food outlets. Further, we conducted a case study and extracted three domains of characteristics for more than 18000 effective takeaway meals from 812 takeaway food outlets located in 10 administrative subdivisions in Haidian District and Xicheng District of Beijing Municipality. The results showed that more than 60% of single meals sold by takeaway food outlets were considered as healthy, and only 15% of takeaway food outlets sold healthy meals exclusively. Additionally, there were significant differences of health effects among different types of food environments, and high-risk areas of different types of food environments can be spatially identified. Compared with the counting method for food environment availability, the proposed new approach can depict food environment characteristics not only in macro-scale like the counting method, but also in meal-scale. The indicators could be useful for large-scale and long-term monitoring of food environmental changes because of their simple calculation and design depending on the food delivery platform.